Involvement of p.R72P and PIN3 Ins16bp (TP53) Polymorphisms and the I157T (CHEK2) Mutation in Breast Cancer Occurrence in Burkina Faso - Dabre, Soayebo; Zoure, Abdou Azaque; Kiendrébéogo, Touwendpoulimdé Isabelle; Zongo, Nayi; Amegnona, Lanyo Jospin; Sombie, Herman Karim; Adico, Marc Donald Wilfried; Bakyono, Bélélé Siméon; Traoré, Lassina; Ouedraogo, Teega-Wendé Clarisse; Alice Ouedraogo, Rogomenoma; M. Zohoncon, Théodora; et al. (Asian Pacific Journal of Cancer Biology, 2023)
Introduction: The TP53 and CHEK2 genes have been described as breast cancer susceptibility genes and some of their polymorphisms have been associated with an increased risk of breast cancer in certain populations. Aim: The objective of this study was to investigate the p.R72P and PIN3 Ins16bp (TP53) polymorphisms and the I157T (CHEK2) mutation developping of breast cancer. Methods: This case-control study had enrolled 144 participants including 65 cases (breast cancer patients) and 79 controls (women without breast abnormalities) in the city of Ouagadougou in Burkina Faso. The DNA was extracted using the method of “salting out” and the genotyping of polymorphisms was performed by ASO-PCR (Allele Specific Oligonucleotides - Polymerase Chain Reaction), conventional PCR and PCR-RFLP (Polymerase Chain Reaction - Restriction Fragment Length Polymorphism) techniques. Results: The heterozygous genotype (RP) of the p.R72P polymorphism of TP53 gene was in the majority in cases (73.85%) and controls (73.42%). Regarding to the PIN3 Ins16bp polymorphism of TP53 gene, the homozygous wild type (A1A1) was the most represented in both cases (53.85%) and controls (60.76%). Concerning the I157T mutation of CHEK2 gene, only one (01) patient was homozygous mutant (TT) and no controls had the mutation. This study found no association between these polymorphisms and the risk of breast cancer occurrence (p.R72P (OR=0.96; 95%IC (0.59-1.56); p=0.471), PIN3 Ins16bp (OR= 1.1; 95%IC (0.61-1.98); p=0.420)). Conclusion: This study showed that the P allele of the p.R72P polymorphism and the wild-type allele (A1) of the PIN3 Ins16bp polymorphism were in the majority. The I157T mutation was very rare. These polymorphisms were not associated with the risk of developing breast cancer in this study.